Balancing Tradition and Modernity: Changing the Image of Woman in Shashi Deshpande’s The Dark Holds No Terrorsand That Long Silence: Exploring the Duality of Tradition and Modernity in Shashi Deshpande's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India has always been rich in its tradition and culture. Indian traditional values give it a unique and different recognition all around the world. It has always attracted western countries and at the same time it has also got affected by the western culture. The westernization of Indian culture gave birth to modernity and now tradition and modernity have become two sides of the same coin. Our tradition offers numerous instances of the spirit of free and critical inquiry of the highest intellectual order and determination to pursue truth. In fact, individuals and cultures derive a lot from their past, mingle it with the experiences of the present and make necessary changes for better future. Change is the part of life and life is a continuous play of two things a desire for change, as well as the need for the familiar and the unknown. All societies have their own tradition but when we talk about ‘traditional societies’, it refers to a specific historical phase of social and cultural development. Tradition is constituted by the beliefs, values, aesthetic, and ways of life,which maintain continuity with the past. Traditional values are passed down from one generation to the next generation without much change. They are the collective wisdom and modes of behaviour of the ancestors, cherished and observed by the present generation. Modernity as opposed to tradition refers an outlook that is generally future oriented and forward looking. Modernization consists of urbanization, industrialization, education, technology, wealth, and diverse occupational opportunities which bring with them a whole new outlook on life, a new system of beliefs, patterns of thoughts. In this fast changing society we witness to many changes from time to time and the clever thing to do is to convert these changes into opportunities.Shashi Deshpande maintains a unique position among the contemporary Indian writers in English. She has a penetrating eye for the fast changing Indian society. She pays much attention to the recent phenomenon of the educated professional woman and her adjustment or maladjustment in the family. Her novels are concerned with the theme of tradition and modernity, an exploration into the female psyche. She has very well portrayed modern, educated and career-oriented middle-class women, who are sensitive to the changing time and situation and shows great balancebetween family and profession. In this paper I have tried to study Shashi Deshpande’s novels The Dark Holds No Terrors and That Long Silence in terms of how her women characters respond to the phenomena of change. Their journey charts, their inner conflict and the balance they maintain between tradition and modernity, in their search for identity, independence, fulfillment, and love in their life.